2007
DOI: 10.1017/s0305000906007719
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the developmental dynamics of subject omission: the role of processing limitations in learning

Abstract: P. Bloom's (1990) data on subject omission are often taken as strong support for the view that child language can be explained in terms of full competence coupled with processing limitations in production. This paper examines whether processing limitations in learning may provide a more parsimonious explanation of the data without the need to assume full competence. We extended P. Bloom's study by using a larger sample (12 children) and measuring subject-omission phenomena in three developmental phases. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 26 publications
(25 reference statements)
1
19
0
Order By: Relevance
“…The authors attributed this age difference in the integration ability to three-year olds' limited capacity to take into account contextual information in communication. This may stem from limited working memory capacity in young children, in line with the findings that young children have limited capacity for language processing as compared to adults (e.g., Bloom, 1970Bloom, , 1990Freudenthal, Pine, & Gobet, 2007). Furthermore, Sekine and colleagues also found that both three-year olds and five-year olds relied more on the speech modality than the gesture modality when they failed to choose the integration match in VG.…”
Section: Discussionmentioning
confidence: 74%
“…The authors attributed this age difference in the integration ability to three-year olds' limited capacity to take into account contextual information in communication. This may stem from limited working memory capacity in young children, in line with the findings that young children have limited capacity for language processing as compared to adults (e.g., Bloom, 1970Bloom, , 1990Freudenthal, Pine, & Gobet, 2007). Furthermore, Sekine and colleagues also found that both three-year olds and five-year olds relied more on the speech modality than the gesture modality when they failed to choose the integration match in VG.…”
Section: Discussionmentioning
confidence: 74%
“…Usage‐based computational accounts of grammatical development have primarily focused on what can be learned from distributional information. This approach has met with considerable success, illuminating the learning of syntactic categories, specific developmental patterns, and the acquisition of construction‐like units, in addition to illustrating the emerging complexity of children's grammatical knowledge more generally . Yet, distributional approaches are unlikely to provide a complete account of children's language use .…”
Section: Introductionmentioning
confidence: 99%
“…Nowhere is this trend more apparent than in developmental psycholinguistics, where, for over three decades (Ref 1), computational models have increasingly contributed to the long-standing debate over the nature of syntax acquisition. Computational modeling-as approach has met with considerable success, illuminating the learning of syntactic categories, 2 specific developmental patterns, 3 and the acquisition of construction-like units, 4 in addition to illustrating the emerging complexity of children's grammatical knowledge more generally. 5,6 Yet, distributional approaches are unlikely to provide a complete account of children's language use.…”
Section: Introductionmentioning
confidence: 99%
“…Bloom 1990). However, Freudenthal et al (2007) demonstrated, using a computational model with an utterance-final bias, that the observed association between the length of the verb phrase and the presence/omission of a subject argument can be explained in terms of performance-limited learning. If children are limited in how much information they are able to learn at any one time, utterances including longer verb phrases are less likely to be fully learned than those with shorter verb phrases, thus sentences with pronominal objects are more likely to be learned with their subject arguments than are those with longer noun phrase objects.…”
Section: Discussionmentioning
confidence: 99%